Accurate determination of the stiffness properties for an elastic interface under peeling conditions between homogeneous materials. (1st April 2022) - Cañas, J.; Blázquez, A.; Estefani, A.; Távara, L.
Abstract: In this paper, several models for analysing peeling tests are considered, including numerical models based on FEM, semi-analytical approaches, and beam models including an elastic interface. Results show that none of the beam models including an elastic interface represents correctly the mixity at the crack tip for small thickness ratios. To avoid this inconsistency, the problem is studied in the framework of Fracture Mechanics, concluding that the stiffness in both directions must fulfil a material-dependent relationship (besides, the tangential stiffness is independent of the shear modulus). The new proposed interface stiffnesses depict accurately both the mixed-mode conditions at the crack tip and the load versus displacement evolution for the full range of thickness ratios.